The Panama Affair. - Simon, Maron J. (New York Charles Scribners sons, 1971)
This is a book worth the purchase if one is interested in how the US-Panama Affair happened, more or less, with a great deal of accurate historical information. There are many authors who have done excellent research on Panamas evolution as a territory and country. With any authority researcher it is equally important to dig deeper into the facts. Panamanians, even before the French negotiator Varilla came on the scene to sell the Panama Canal to the US, were at the brink of political exhaustion under Colombian rule.
Keywords: Science